Application of hydrosurgical debridement and autologous skin cell suspension in the treatment of electric arc injury - Yu Feng Guo; Xin Gang Song; Guo Rong Song; Yun Wei Duan; Wei Ping Zhu (Elsevier, 2022)
The majority of electric arc injury wounds are deep second-degree or mixed depth wounds. Traditional treatment methods in these types of injuries have many shortcomings. This randomized prospective study evaluated the use of a minimally invasive hydrosurgery system for precise debridement, followed by the application of autologous skin cell suspension prepared utilizing the RECELL® Autologous Cell Harvesting Device (AVITA Medical). Compared with traditional methods, the cases treated with hydrosurgical debridement and autologous skin cell suspension had improved healing times and scar appearance after healing. The combination of these two treatment modalities appears to restore function and appearance for electric arc injuries.